2021
DOI: 10.48550/arxiv.2102.12423
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimal dynamic regulation of carbon emissions market: A variational approach

Abstract: We consider the problem of reducing the carbon emissions of a set of firms over a finite horizon. A regulator dynamically allocates emission allowances to each firm. Firms face idiosyncratic as well as common economic shocks on emissions, and have linear quadratic abatement costs. Firms can trade allowances so to minimise total expected costs, from abatement and trading plus a quadratic terminal penalty. Using variational methods, we exhibit in closed-form the market equilibrium in function of regulator's dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(45 reference statements)
1
0
0
Order By: Relevance
“…The insights of Proposition 1 differ, but remain consistent with extant academic literature (Li, 2013(Li, , 2014(Li, , 2016. For instance, the study by Aïd and Biagini (2021) revealed that the optimal abatement effort increases with the tax rate and the marginal pollution damage. This finding aligns with the results presented in (11a), where the abatement effort, u, increases with the tax rate, τ , and the degradation of pollution, δ. Additionally, the survey of Chen et al (2020) found that product prices increase with the marginal pollution damage.…”
Section: Optimal Policies and Relationshipssupporting
confidence: 70%
“…The insights of Proposition 1 differ, but remain consistent with extant academic literature (Li, 2013(Li, , 2014(Li, , 2016. For instance, the study by Aïd and Biagini (2021) revealed that the optimal abatement effort increases with the tax rate and the marginal pollution damage. This finding aligns with the results presented in (11a), where the abatement effort, u, increases with the tax rate, τ , and the degradation of pollution, δ. Additionally, the survey of Chen et al (2020) found that product prices increase with the marginal pollution damage.…”
Section: Optimal Policies and Relationshipssupporting
confidence: 70%